Potential link between transfusion-transmitted infections and ABO and Rh blood group systems in healthy blood donors - Aneesha Kataria; Durre Aden; Sabina Khan; Meesa Mehraj; Yasir Alvi; Sujata Jetley (MGM Journal of Medical Sciences)
Background: Screening blood donations is essential to prevent transfusion-transmitted infections (TTIs). Research indicates that ABO and Rh blood groups might influence infection transmission risks. Materials and Methods: This retrospective study examined data from 10,470 healthy blood donors over seven years (2016–2022) at a tertiary care hospital. Blood typing was performed for ABO and Rh groups, and all voluntary and replacement donors were screened for TTI markers—hepatitis B virus (HBV), hepatitis C virus (HCV), human immunodeficiency virus (HIV), malaria, and syphilis—using third-generation ELISA kits, rapid tests, rapid plasma reagin (RPR), and venereal disease research laboratory (VDRL). Statistical analyzes were conducted using Chi-square and Fisher’s exact test in Statistical Package for Social Sciences version 26.0. Results: Among the 10,470 male donors screened, 173 were replacement donors, and 6 were voluntary donors. TTI positivity was identified in 1.79% of donors, with the following breakdown: 69.27% positive for hepatitis B, 15.6% for hepatitis C, 11.7% for HIV, and 5% for syphilis. The highest TTI prevalence was observed in the B blood group (43%), followed by O (30.16%), A (21.78%), and AB (6.7%). Overall, Rh-positive individuals were more susceptible, and a significant association was observed between Rh-negative donors and HBV infection. Conclusion: The B-positive blood group showed the highest seroprevalence for TTIs. However, no statistically significant association was found between TTI prevalence and ABO or Rh blood group systems.